The Impact on Rent from Tenant and Landlord Characteristics and Interaction - Erling Røed Larsen; Dag Einar Sommervoll (Statistics Norway, Research Department, 2006)
Owner-occupied housing services and rented housing services are often considered close substitutes, and both house price and rental price indices rely on regressions based on dwelling and location characteristics. However, while such characteristics are exhaustive in the owner's market, they cannot capture the additional complexity of rental markets. This paper offers a theoretical framework and an empirical analysis of additional factors that affect rent. The factors comprise three categories: Landlord characteristics, tenant characteristics, and characteristics of the landlord-tenant interaction. We analyze a novel data set sampled from the Norwegian rental market and obtain substantial improvements in explanatory power by including information on tenant and landlord characteristics and interaction. While variation in geographical variables explains 17 percent of the variation in monthly rent; variation in hedonic variables explain only 12 percent. Variation in tenant and landlord characteristics and interaction explains as much as 15 percent of rent variation. The full model captures 44 percent of rent variation and offers insights into the monetary values of landlord type, market mediation, tenure length, tenant type, and services. This additional explanatory power accentuates the difference between the owner's and renter's market, and the results come with ramifications for the general understanding of the rental market, for construction of rental indices, and for the assumption of a rental-equivalence principle in CPI-construction.
Keywords: C21; D12; R21; 330; hedonic regression; housing market; landlord; rent; rental index; rental market; tenant.